Fuscmacula, a new leafhopper genus from China (Hemiptera: Cicadellidae: Deltocephalinae) - Yao, Binbin; Zhang, Runzhi; Xing, Jichun (Zootaxa, 2021)
A new leafhopper genus of Athysanini from China, Fuscmacula gen. nov. with F. biprocessa sp. nov. as type species is described and illustrated. This species was collected from grass. The type specimens of the new species are deposited in the Institute of Entomology, Guizhou University, Guiyang, China (GUGC).